Identification and Prioritization of Effective Sports Policies for National Security Development: A Mixed-Methods Policy Framework - Yari, Mehdi; Khorvash, Majid; Moshkelgosha, Elham (Journal of Foresight and Health Governance, 2026)
This study aimed to identify and prioritize sports policies that contribute to national security development. Using a sequential exploratory mixed-methods design, the research integrated constructivist grounded theory with the TOPSIS multi-criteria decision-making technique. In the qualitative phase, 16 experts from sport governance, national security institutions, and academia were selected through purposive and snowball sampling. Semi-structured interviews were analyzed using focused coding, leading to the identification of 32 policy actions grouped into eight strategic themes: roadmap design, inter-sectoral coordination, infrastructure development, support for specific groups, international engagement, alliance-building, sport promotion, and cultural development and support. In the quantitative phase, these policies were prioritized through TOPSIS based on expert weighting. Results indicated that “improving the country’s international image” ranked first, followed by “strategic policymaking and training,” and “strengthening diplomatic relations.” Findings highlight that soft power-oriented and sport diplomacy-based policies exert the greatest perceived impact on national security. The study provides a structured decision-making framework enabling policymakers to allocate resources more strategically. By moving beyond descriptive analysis of sport-security relationships, this research contributes a prescriptive and operational roadmap for leveraging sport as an instrument of national resilience and geopolitical positioning.